Exfoliation of Few‐Layer Graphene in Volatile Solvents Using Aromatic Perylene Diimide Derivatives as Surfactants. Issue 3 (30th November 2016) - Liscio, Andrea; Kouroupis‐Agalou, Konstantinos; Kovtun, Alessandro; Gebremedhn, Elias; El Garah, Mohamed; Rekab, Wassima; Orgiu, Emanuele; Giorgini, Loris; Samorì, Paolo; Beljonne, David; Palermo, Vincenzo
Abstract: Commercial, aromatic perylene diimide (PDI) dyes were used to exfoliate few‐layer graphene nanosheets in low‐boiling organic solvents such as chloroform and tetrahydrofuran. Importantly, in such solvents, graphene cannot be exfoliated in the absence of the aromatic perylene diimide (PDI) dyes. The PDIs are physisorbed onto the basal plane of the nanosheet surface, which stabilized them in solution; the aromatic core lies flat on graphene and the PDI side groups influenced the physisorption strength and molecular packing. Upon varying just a single atom in the chemical structure of the side groups, significantly different exfoliation efficiencies were observed. The graphene–PDI interaction was studied at the nanoscale by scanning tunneling microscopy and molecular dynamics, at the microscale by atomic force and electron microscopy, and at the macroscale by optical spectroscopy. Thanks to the high volatility of the chosen solvent, the nanosheets can be embedded in standard polymer composites through a simple solvent‐induced swelling procedure. Abstract : Liquid exfoliation is one of the most promising techniques for the mass production of graphene and its processing into useful materials. Here, a viable approach compatible with large‐scale industrial application in the polymer industry is presented. The approach is based on commercial molecules such as aromatic perylene diimide dyes for the exfoliation of few‐layer graphene nanosheets in low‐boiling organic solvents (see figure).